2010
DOI: 10.1143/jjap.49.07hf21
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Localized Heating by Ultrasonically Induced Cavitation in High Intensity Focused Ultrasound Treatment

Abstract: There are reports that ultrasonically induced cavitation bubbles locally enhance tissue heating in high intensity focused ultrasound (HIFU) treatment. In this study, a high-intensity burst (named ''a triggering pulse'') above the cavitation threshold was used to trigger cavitation. Immediately after that, CW ultrasound (named ''heating waves''), at an intensity level and duration typical for conventional HIFU ablation was irradiated. Before the ablating sonication, it is necessary to determine the optimum inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 8 publications
0
54
0
Order By: Relevance
“…The above-described problem is expected to be overcome by utilizing such cavitation microbubbles. We have proposed cavitationenhanced HIFU treatment using an exposure sequence, [5][6][7][8] which we named the "trigger HIFU" sequence, consisting of a highly intense short "trigger pulse" to generate cavitation and an immediately following moderate-intensity long "sustaining burst" to oscillate the generated microbubbles. The effectiveness of the proposed exposure sequence has been confirmed in regard to the thermal effect of ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…The above-described problem is expected to be overcome by utilizing such cavitation microbubbles. We have proposed cavitationenhanced HIFU treatment using an exposure sequence, [5][6][7][8] which we named the "trigger HIFU" sequence, consisting of a highly intense short "trigger pulse" to generate cavitation and an immediately following moderate-intensity long "sustaining burst" to oscillate the generated microbubbles. The effectiveness of the proposed exposure sequence has been confirmed in regard to the thermal effect of ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Takagi et al (2010) and Nakamura et al (2013) used a © 2010 IEEE high-intensity burst above the cavitation threshold to generate cavitation bubbles in chicken fillets, immediately followed by application of a low-intensity continuous-wave ultrasound at a certain intensity level and duration to sustain the triggered cavitation and to heat the tissue (Fig. 6.65).…”
Section: Multiple-amplitude Enhanced Ablationmentioning
confidence: 99%
“…First, phase-shift nanoemulsions (PSNEs) which are sensitive to both temperature and acoustic pressure, and their response to environmental changes should be comprehensively studied. Second, systems that use a combination of multiple waves with different amplitudes have also been investigated to enhance cavitation effect (Takagi et al 2010). We discuss these two cases in Sects.…”
mentioning
confidence: 99%
“…Although increased heat depositions were obtained using microbubbles in the previous research, distorted coagulation regions or temperature distribution were observed, such as tad-pole shaped [12,22,24] or pre-focal [13,19,[24][25][26] heating regions. A "trigger 2 of 20 HIFU" sequence that consists of high-intensity short pulses and following moderate-intensity long bursts has been investigated to avoid such distorted coagulation regions while enhancing the ultrasonic heating [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%